Angioleiomyoma (Vascular Leiomyoma) of the Oral Cavity - Rawal, Swati Y. (Head Neck Pathol, 2017)
A 70-year-old male presented with a slow growing, dome shaped and painless mass of the hard palate. The mass was excised. Histopathological examination confirmed the diagnosis of a angioleiomyoma (vascular leiomyoma). A leiomyoma is an uncommon benign tumor of smooth muscle differentiation. True leiomyomas of the oral cavity are rare and most oral tumors are derived from the smooth muscle of walls of blood vessels. Therefore, they are called vascular leiomyomas or angioleiomyomas. Clinically, they may resemble a myriad other conditions both benign and malignant. A definitive diagnosis depends upon histopathological examination of the biopsied tissue in correlation with the tumor cell immunohistochemistry. Tumors are excised and recurrence is rare. The histopathological findings and differential diagnosis of a case of a palatal angioleiomyoma are discussed.